2019
DOI: 10.1097/gme.0000000000001200
|View full text |Cite
|
Sign up to set email alerts
|

Association of menopause and type 2 diabetes mellitus

Abstract: The prevalence of T2DM is high among women, and postmenopause status might be a stable and significant risk factor for T2DM; especially, postmenopausal women with normal weight should not be ignored in addressing the risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 24 publications
3
34
1
3
Order By: Relevance
“…Two studies have shown that menopause has a marked effect on the circulation levels of lipids and lipoproteins, with an especially significant increase in LDL-C levels [32, 33]. Previous studies have examined the association between FPG, 2hPG and CVD risk in a community [18, 34, 35]. These studies have reported significant results, which are consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Two studies have shown that menopause has a marked effect on the circulation levels of lipids and lipoproteins, with an especially significant increase in LDL-C levels [32, 33]. Previous studies have examined the association between FPG, 2hPG and CVD risk in a community [18, 34, 35]. These studies have reported significant results, which are consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…At menopause, women experience health challenges due to estrogen deficiency. The risk of T2DM is increasing with post-menopause status interacting with other risk factors, that is, hypertension, dyslipidemia, and obesity (Ren et al, 2018). Estrogen may regulate insulin action directly via actions on insulin-sensitive tissues.…”
Section: Discussionmentioning
confidence: 99%
“…At menopause, women experience health challenges due to estrogen deficiency. The risk of T2DM is increasing with postmenopause status interacting with other risk factors i.e hypertension, dyslipidemia and obesity (Ren et al 2018). Estrogen may regulate insulin action directly via actions on insulin-sensitive tissues.…”
Section: Discussionmentioning
confidence: 99%